Optymalizacja liczby skoków przygotowawczych przed wykonaniem wybranych skoków na trampolinie przez zawodników wyczynowych = Optimalization of the number of preparatory jumps before performing selected jumps on the trampoline by professional competitors - Kosendiak, Jan; Hes, Bartłomiej; Rogoziński, Jakub (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In many sports disciplines, competitors perform activities that are not directly evaluated by referees, and whose time, length, or height are not directly measured, but which determine good sports results. In the case of trampolining, such activities involve the jumps that precede the program during competitions. Those preparatory jumps help the competitor perfom jumps for which he can receive the best notes. By undertaking research on the importance of preparatory activities in trampoline jumps, the authors decided to discover the interdependence between the number of preparatory jumps and the quality of the performance.
Keywords: gimnastyka; skoki na trampolinie; skoki przygotowawcze; gymnastics; trampoline jumps; preparatory jumps